ANALISIS KEMANTAPAN LERENG LOW WALL PIT-1 MTBU MENGGUNAKAN HASIL PENGUKURAN EXTENSOMETER DI PT. TAMBANG BATUBARA BUKIT ASAM - aryanto, M
ABSTRACT: The stability analysis of low wall slope of Pit-1 MTBU in PT. Tambang Batubara Bukit Asam (Persero), was done with dynamic and static analysis, which used elasticity modulus (E) and Poisson's ratio (v) produced from back analysis. Dynamic analysis was done because there was vibration factor in investigation site caused by waste and coal transportation, and back analysis was done with data of rock mass displacement obtained from the result of Extensometer and slip stick measurement. Modulus elasticity and Poisson's ratio 95% from laboratory test was obtained based on the result of dynamic and static analysis. The rock mass displacement produced from dynamic and static analysis is not obviously different, but safety factor produced from both is significantly different. Dynamic analysis produced safety factor SF = 1.00, while static analysis produced safety factor SF = 2,0 on toe of low wall slope. The effort to stabilise of low wall slope can be done by reducing the dip of overall slope. Dynamic analysis with simulation model which has overall slope (3 = 20Â°, produced safety factor distribution SF > 1.5 on every part of the model.